PENGARUH EFIKASI DIRI DAN LOCUS OF CONTROL TERHADAP KINERJA PEGAWAI PADA DINAS KETAHAN PANGAN DAN PETERNAKAN PROVINSI SUMATERA SELATAN - Cici Ria Agustini; Rismansyah Rismansyah; Edduar Hendri (Universitas Nusa Cendana, 2023)
The purpose of this study is to determine the effect of Self-Efficacy and Locus of Control on Employee Performance. The method used in this research is quantitative. In this study, the population was 2009 employees at the food security and animal husbandry of the province of South Sumatera. This study uses a non-probability sampling technique that is purposive sampling. In this study, the sample as the criteria was 104 permanent employees. The data analysis technique is Multiple Linear Regression using the SPSS 21 for Windows. Based on the findings of hypothesis testing, it shows that there is a partial influence between the variable Self-Efficacy on Employee Performance there is a partial influence between the Locus Of Control variable on Employee Performance, and there is a simultaneous effect between the variables of Self Efficacy and Locus Of Control on Employee Performance at Dinas Ketahanan Pangan dan Peternakan Provinsi Sumatera Selatan. Keywords: Self-Efficacy; Locus of Control; Employee Performance